User Interaction Patterns on User-Generated Content of Hindia's Song "Membasuh" on the TikTok Application - Dede Wahyuni Wahyuni; Weni Adityasning Arindawati; tri susanto (Metacommunication: Journal of Communication Studies, 2025)
The use of Hindia's song Membasuh on the TikTok platform has given rise to various forms of User Generated Content (UGC) that share similar narratives, particularly in expressing emotions, life experiences, and social awareness values in the digital space. This study aims to analyze the patterns of interaction and meaning of communication formed in the comment section of the UGC, in order to understand how users construct shared meaning through participatory culture on social media. The approach used is qualitative with a netnography method. Data was collected from two UGC contents with the highest interaction rates and processed using two web-based tools, namely Apify Consol to extract comments and Voyant Tools to analyze the text. Furthermore, the data was analyzed using Braun and Clarke's thematic analysis combined with Miles and Huberman's model through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that interactions in the comments section form two main themes, namely personal experience reflection and emotional support. In conclusion, the comments section on UGC Membasuh acts as a digital social space that encourages self-expression, empathy, and interconnection among users, while also confirming that music functions as a medium of emotional communication and a means of social interaction in today's digital culture.